Relationship between the kinematical factors and the ball velocity of the penalty corner drag-flick in field hockey - Wali, R.; Iqbal, Y. (Global Social Sciences Review, 2022)
The aim of the study was to analyze the relationship of the kinematical factors with the ball velocity of the drag flick performance of the national elite players in field hockey. To attain this purpose, 64 drag flicks of sixteen players were recorded and analyzed through the VICON motion capture system and MATLAB software. The descriptive statistics and Spearman correlation were computed for statistical analysis. The mean ball velocity of the drag-flicks of the female and male players were 21.31±3.53 m/s and 15.10±4.02 m/s, respectively. The ball dragging length, ball dragging velocity, stance width, left-knee angle and left elbow angle had a significant correlation with the ball velocity. The subjects maximize dragging length, dragging velocity and stance width while minimizing their left-right knee angles for high velocity. Players and coaches should emphasize ball dragging length, dragging velocity and stance width to improve the drag flick performance.